Estudio estructural de penetración de Aspergillus parasiticus al cariópside de Zea mays - Córdoba Cedeño, Hernán D. (1994)
The foremost area of penetration of Aspergillus parasiticus Speare to the caryopsis of corn (Zea mays L.) shell and in ear, was observed through scanning electron microscopy. A. parasiticus colonized the epidermal tissues of the bract, the tip cap, pericarp and the remanent oi silk. In addition, the fungus colonized the tip cap tissue exposed to ment of A. parasiticus took place mainly, through the continous intercellular spaces between the spongy parenchyma of the tip cap and the proximal pericarp. Seventy-two hours after inoculation the proximal pericarp of shelled corn, was always colonized by A. parasiticus, in contrast, invasion of the proximal pericarp of corn in the ear was observed only once, The results of this work indicates that the spongy tissue of tip cap normally exposed to the mechanic action of the shell, is the main area of penetration of A. parasiticus to the caryopsis. The results also indicate that the shelled corn is invaded more frequently than leaf on the ear.